2019
DOI: 10.2147/copd.s223354
|View full text |Cite
|
Sign up to set email alerts
|

<p>The Screening Value Of ESS, SACS, BQ, And SBQ On Obstructive Sleep Apnea In Patients With Chronic Obstructive Pulmonary Disease</p>

Abstract: Objective: To compare the performance of Epworth sleepiness scale (ESS), sleep apnea clinical score (SACS), Berlin questionnaire (BQ), and STOP-BANG questionnaire (SBQ) in screening for obstructive sleep apnea (OSA) in patients with chronic obstructive pulmonary disease (COPD). Methods: A total of 431 patients were analyzed. All subjects completed lung function test, ESS, SACS, BQ, and SBQ survey and overnight polysomnography (PSG). According to lung function and PSG results, participants were divided into COP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(26 citation statements)
references
References 34 publications
(52 reference statements)
1
11
0
Order By: Relevance
“…Multiple regression analysis showed that patients with COPD and coexisting OSA had higher CAT, ESS, CCI, and SBQ scores compared with patients with COPD alone. These findings were in line with previous studies that showed positive relationships between OSA and CAT, ESS, CCI, and SBQ scores in patients with COPD [ 28 , 39 ]. This suggested that patients with COPD overlapping with OSA had more-severe clinical symptoms, more-limited daily activities, more complications, and poorer sleep quality and quality of life.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Multiple regression analysis showed that patients with COPD and coexisting OSA had higher CAT, ESS, CCI, and SBQ scores compared with patients with COPD alone. These findings were in line with previous studies that showed positive relationships between OSA and CAT, ESS, CCI, and SBQ scores in patients with COPD [ 28 , 39 ]. This suggested that patients with COPD overlapping with OSA had more-severe clinical symptoms, more-limited daily activities, more complications, and poorer sleep quality and quality of life.…”
Section: Discussionsupporting
confidence: 93%
“…We found a correlation between COPD severity and OSA. Compared with patients with COPD alone, patients with COPD plus OSA had higher FEV 1 , FEV 1 % of predicted value, and FEV 1 /FVC, and a lower proportion of severe COPD [ 26 – 28 , 39 ]. The incidence of OSA increased with increasing airflow restriction in COPD patients with AHI < 5 events per hour, and decreased with increasing airflow restriction in COPD patients with AHI > 30 events per hour.…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, DCA, NRI, and IDI indicated that at a probability threshold of >42%, the nomogram was more clinically beneficial and could better predict OSA than the ESS. STOP-Bang was initially used to screen surgical patients [ 40 ], and its ability to predict mild, moderate, and severe OSA was higher than that of the sleep apnea clinical score, BQ, and ESS [ 41 ]. However, the AUC of OSA for all degrees of severity (0.72) was lower than that of our model [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…These ndings were in line with previous studies that showed positive relationships between OSA and CAT, ESS, CCI, and SBQ scores in patients with COPD. 28,39 This suggested that patients with COPD overlapping with OSA had more-severe clinical symptoms, more-limited daily activities, more complications, and poorer sleep quality and quality of life. Although our ndings suggested that the SBQ could be used for OSA screening, hypertension and male sex were the main contributory factors, while BMI and neck circumference were less important.…”
Section: Discussionmentioning
confidence: 99%
“…Compared with patients with COPD alone, patients with COPD plus OSA had higher FEV 1 , FEV 1 % of predicted value, and FEV 1 /FVC, and a lower proportion of severe COPD. [26][27][28]39 The incidence of OSA increased with increasing air ow restriction in COPD patients with AHI <5 events per hour, and decreased with increasing air ow restriction in COPD patients with AHI >30 events per hour. Compared with patients with mild and moderate air ow restriction, the proportion of AHI <5 events per hour was higher and the proportion of AHI >30 events per hour was lower in patients with severe air ow restriction.…”
Section: Discussionmentioning
confidence: 99%